The development of medical infographics to raise symptom awareness and promote communication to patients with cancer: A co-creation study - Karin Piil; P. Pedersen; H. Holm Gyldenvang; A. Juhl Elsborg; A. Bascuñan Skaarup; M. Starklint; T. Kjølsen; H. Pappot (Elsevier, 2023)
Objective: The study aims to develop medical infographics that have a potential to raise symptom awareness and promote symptom communication between patients diagnosed with cancer and healthcare professionals. Methods: This study comprised four phases: 1) development of medical infographics, 2) user testing with healthcare professionals and patients, 3) selection of specific medical infographics, and 4) interviews on these specific medical infographics with patients using the think-aloud method. Results: Design students created 22 medical infographics conveying information about six symptoms and concerns. Patients (n = 28) with cancer said that the colourful infographics evoked individual emotional responses and associations, and they facilitated their narratives of experiences with symptoms. Healthcare professionals (n = 29) thought the infographics were eye-catching and may promote dialogue on symptoms. Conclusions: The design of medical infographics must target a specific population. When introduced, the use of medical infographics may be influenced by the physical surroundings. Medical infographics can facilitate symptom communication by creating symptom awareness and providing patients with the vocabulary to describe their symptoms and concerns. Innovation: Medical infographics are engaging visual messages with the potential to help prepare cancer patients to communicate their symptom experiences and reduce the feeling of being alone in experiencing certain symptoms.